Numerical analysis of radiant warmer - Rojczyk, Marek; Szczygieł, Ireneusz (Computer Assisted Methods in Engineering and Science; Vol 20 No 3 (2013), 2017)
The main objective of this paper is to recognise the heat transfer phenomena between an infant placed in a radiant warmer and the surrounding environment. The influence of the parameters in the computational time during different physical phenomena in heat transfer is studied. This model can be also used in future work to improve radiant warmer efficiency. A complete 2D and 3D numerical simulation was carried out using commercial code ANSYS Workbench- ANSYS Fluent. The analysis involved the fluid flow, convection and radiation heat transfer as well as turbulence modeling, although moisture phenomena were omitted. The experiments were completed to validate a numerical solution.